P43 Hyperpolarised xenon-129 MRI of lungs in healthy volunteers: a safety & feasibility study. (15th November 2016) - Safavi, S; Thorpe, J; Haywood, B; Barlow, M; Hall, IP
Abstract : Introduction: Conventional proton MRI, although non-invasive and non-ionising, is of little value in imaging the lungs due to poor signal intensity. Hyperpolarised xenon-129 MRI (129Xe-MRI) is a novel technique developed to enhance the applicability of MRI in lung imaging. It has the potential to provide not only anatomical data but also regional lung function data, particularly as xenon is highly lipophilic, and can be use as a gas exchange probe. Aim: We aimed to assess the feasibility and tolerability of 129Xe-MRI in healthy adult volunteers. Method: This was a single centre prospective observational study. Ethical approval had been obtained. The volunteers had provided written informed consent. A GE 2000 polariser was used for production of hyperpolarised 129Xe, with a 1.5T GE MRI scanner for imaging. The volunteers underwent a conventional MRI thorax, followed by 129Xe-MRI of lungs. The inhaled volume of hyperpolarised 129Xe ranged 0.6–1.0L. There was 30 minutes of observation with recording of vital signs, i.e., oxygen saturations (O2 sats), heart rate (HR), and blood pressure (BP) at 5, 10, 15, and 30 minutes post-inhalation of xenon, after each scan. Each visit comprised of a maximum of four scans. Results: Nine volunteers (male: female 8:1, aged 20–34) underwent 28 scan visits, comprising of 102 scans. 129Xe-MRI was well-tolerated, with no serious adverse events. The polarisation achieved ranged 4.10–10.57%. To assess the impact of inhaling xenon on vital signs as a safety measure, the recorded vital signs were analysed using student's t-test. There was no significant change in O2 sats or BP. The most notable change was noted in HR, which was persistently reduced following inhaling xenon (p < 0.001). These changes were not deemed clinically significant. We achieved good image quality (Figure 1 ). Spectroscopy distinguished lung tissue-dissolved xenon from blood-dissolved. Dissolved phase imaging (DPI) was obtained. The technique was reproducible. Discussion: The data demonstrates satisfactory feasibility and tolerability of 129Xe-MRI. DPI can image regional gas exchange. 129Xe-MRI may be used to develop biomarkers of disease progression, and assess drug efficacy, to personalise medicine, reduce healthcare costs, and lower cost and duration of drug development.